Leukocyte function-associated antigen-1/intercellular adhesion molecule-1 interaction induces a novel genetic signature resulting in T-cells refractory to transforming growth factor-β signaling. - Volkov, Yuri; Kelleher, Dermot; Long, Aideen; Fallon, Padraic; Verma, Navin K.; Dempsey, Eugene; Davies, Anthony; Barry, Sean P. (My University, 2012)
The immunesuppressive cytokine TGF-β plays crucial regulatory roles in the induction and maintenance of immunologic tolerance and prevention of immunopathologies. However, it remains unclear how circulating T-cells can escape from the quiescent state maintained by TGF-β. Here, we report that the T-cell integrin leukocyte function-associated antigen-1 (LFA-1) interaction with its ligand intercellular adhesion molecule-1 (ICAM-1) induces a genetic signature associated with reduced TGF-β responsiveness via up-regulation of SKI, E3 ubiquitin-protein ligase SMURF2, and SMAD7 (mothers against decapentaplegic homolog 7) genes and proteins. We confirmed that the expression of these TGF-β inhibitory molecules was dependent on STAT3 and/or JNK activation. Increased expression of SMAD7 and SMURF2 in LFA-1/ICAM-1 cross-linked T-cells resulted in impaired TGF-β-mediated phosphorylation of SMAD2 and suppression of IL-2 secretion. Expression of SKI caused resistance to TGF-β-mediated suppression of IL-2, but SMAD2 phosphorylation was unaffected. Blocking LFA-1 by neutralizing antibody or specific knockdown of TGF-β inhibitory molecules by siRNA substantially restored LFA-1/ICAM-1-mediated alteration in TGF-β signaling. LFA-1/ICAM-1-stimulated human and mouse T-cells were refractory to TGF-β-mediated induction of FOXP3+ (forkhead box P3) and RORγt+ (retinoic acid-related orphan nuclear receptor γt) Th17 differentiation. These mechanistic data suggest an important role for LFA-1/ICAM-1 interactions in immunoregulation concurrent with lymphocyte migration that may have implications at the level of local inflammatory response and for anti-LFA-1-based therapies.
Keywords: Immunesuppressive cytokine; Gene regulation; Immunology; Integrin; Lymphocyte; Transforming Growth Factor Beta (TGFbeta); Immunology, Inflammation & Infection; Biomedical sciences